Deterioration and Predictive Condition Modeling of Concrete Bridge Decks Based on Data from Periodic NDE Surveys - Kim, Jinyoung; Gucunski, Nenad; Dinh, Kien (Journal of Infrastructure Systems, 2019)
A novel approach and program are developed for deterioration and predictive modeling of concrete bridge decks based on nondestructive evaluation (NDE) data. Through an iterative process - combined with data processing, bridge deck segmentation, regression analysis, data integration, and deterioration and predictive modeling - the developed program aids estimates of the remaining service life of bridge decks. Data collected on an actual bridge deck during a period of five and half years are used to illustrate the operation and performance of the developed program. Based on evaluation of condition maps, condition indices, and deterioration curves developed for a range of input parameters, the proposed method quantifies progression of deterioration in bridge deck. By reviewing the predictive models, combined with segmentation of the bridge deck area, a more realistic and practical estimation of the deck's remaining service life can be made. It is anticipated that the proposed method will provide objective and comprehensive evaluation and prediction of bridge deck condition based on data from multiple NDE technologies.
Keywords: Comprehensive evaluation; Condition index; Input parameter; Iterative process; Non destructive evaluation; Practical estimation; Predictive modeling; Predictive models; Bridge decks; Concrete; Deterioration and predictive modeling; Nondestructive evaluation; Segmentation